Parenting Skills According to The Islamic Perspective Towards Family Well-Being - Zur Raffar, Izzah Nur Aida; Hanin Hamjah, Salasiah; Hasan, Ahmad Dzaky; Nik Dahlan, Nang Naemah (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
Parents are leaders of the family who should play the role of building family well-being. Family well-being very much depends on the way of nurturing or raising and managing the family. In order to build a prosperous or happy family, the first and foremost matter which needs to be emphasised is parenting knowledge. Neglecting this parenting aspect will result in parents’ failure to effectively manage the family toward well-being, even causing suffering to children and is associated with bad behaviour such as committing murder, physical or sexual abuse, and neglecting their education. Hence, this research is conducted to study parenting skills according to the Islamic perspective, by using content analysis method. Research findings based on the views of Muslim scholars conclude that in the Islamic perspective, the parenting skills which parents need to master to become excellent parents are parenting knowledge, maintaining their relationship with Allah SWT, relationship with their children and relationship with fellow human beings,  encompassing spiritual, mental, emotional, physical and social aspects. The implications of this research can help parents know the basic parenting skills according to the Islamic perspective, to build a prosperous family. This research also contributes knowledge to the authorities responsible for managing family development so that knowledge, skills and programs relating to parenting can be disseminated and practised in Muslim family life.